Ideas of Student Mobility in Germany - Teichler, Ulrich (International Higher Education, 2012)
German universities have a special approach to student mobility. No extra fees are charged and tuition is often entirely free for foreign students, whether from within the Bologna area or outside. Policies have evolved as a result of experience with the Erasmus program.